Bladder outlet obstruction disrupts circadian bladder function in mice - Kitta, Takeya (Sci Rep, 2020)
The circadian clock programs daily rhythms and coordinates multiple behavioural processes, including micturition. Partial bladder outlet obstruction (pBOO) in mice produces hyperactive voiding. However, long-term effects of pBOO on bladder function have not been clarified. In this study, we investigated micturition under conditions of impaired circadian bladder function by inducing long-term pBOO by tying the proximal urethra. Micturition behavior was evaluated at 1, 3, 6 and 12 months after surgery. We used automated voided stain on paper method for a precise micturition recording for mice. And quantitative assessment of gene expression was performed at 24 months after pBOO surgery using qRT-PCR procedure. The micturition frequencies in the pBOO group were significantly decreased at 3, 6, and 12 months compared to those at 1 month after operation in the same group (p < 0.05). Body weight of pBOO mice was significantly increased compared to sham operated mice at 12 months. The expression level of mRNA was exhibited a 3.4-fold nominal increased for a 5-HT2B receptor in the pBOO group compared to the sham group. The current study found that long-term pBOO led to disruption of the circadian bladder function (the day/night cycle) in mice, similar to those observed in human as nocturia. This disruption is possible involvement of the gain of body weight and/or serotonergic alteration after pBOO.